SoC Design Approach Using Convertibility Verification. (31st December 2008) - Sinha, Roopak; Roop, Partha S.; Basu, Samik
Abstract : Compositional design of systems on chip from preverified components helps to achieve shorter design cycles and time to market. However, the design process is affected by the issue of protocol mismatches, where two components fail to communicate with each other due to protocol differences. Convertibility verification, which involves the automatic generation of a converter to facilitate communication between two mismatched components, is a collection of techniques to address protocol mismatches. We present an approach to convertibility verification using module checking. We use Kripke structures to represent protocols and the temporal logicACTL to describe desired system behavior. A tableau-based converter generation algorithm is presented which is shown to be sound and complete. We have developed a prototype implementation of the proposed algorithm and have used it to verify that it can handle many classical protocol mismatch problems along with SoC problems. The initial idea forACTL -based convertibility verification was presented at SLA++P '07 as presented in the work by Roopak Sinha et al. 2008.